Specific Causes of Friction and Vibration (Eurasian Journal of Engineering and Technology, 2022)
This article is devoted to spasmodic displacements of surfaces. Practically observed oscillations have a small frequency. The true cause of the friction jumps is determined. It is established that the friction force from a place is a given increasing function. An analysis of the phenomenon of jumps during friction is considered using the example of a slip of a body relative to a rough plane. After the end of the first jump, the body has uniform motion, then the second jump according to the harmonic law again has uniform motion, etc.